Restriction of nodulation by the broad host range Rhizobium tropici strain CIAT899 in wild accessions of Phaseolus vulgaris L. - Kipe-Nolt, Judith A.; Montealegre, CM; Tohme, Joseph M. (Wiley, 1992)
Common bean (Phaseolus vulgaris L.) is nodulated by a heterogeneous group of Rhizobium strains. In a search for host plant restriction of nodulation by some of these strains, 50 wild and cultivated bean accessions were evaluated for the length of time taken to form effective nodules with three diverse bean strains. As bean genotypes vary substantially for this character, preference or restriction was defined as a relative parameter between the three Rhizobium strains for a given bean genotype. Many of the bean genotypes evaluated showed no preference for particular strains of Rhizobium though Rhizobium strain CIAT8002 was often slowest to nodulate. Amongst the wild and landrace bean accessions, there was a tendency for materials of Mesoamerican origin to form active nodules more rapidly with CIAT632 (a Rhizobium leguminosarum bv. phaseoli strain isolated from Guatemala) than with CIAT899 (a broad host-range, R. tropici from Colombia). In contrast, in those cases in which some preference was observed, wild and landrace bean genotypes from Peru and Argentina (Andean origin) nodulated more rapidly with Rhizobium strain CIAT899. There were exceptions to this pattern among bred lines. Three wild bean accessions: G10002 from Mexico, G23418 from Costa Rica and G21117 from Colombia showed strong resistance to nodulation with CIAT899. Formation of effective nodules took more than 10 d longer with CIAT899 than with CIAT632. This strain preference was not altered by changing the time of inoculation between 0 and 8 d after sowing. Within an accession, plant to plant variation was observed in the time taken to nodulate with a given strain of Rhizobium. However this variation persisted in the progenies of contrasting individual plants of G21117.